Effect of Cultivar and Agroecological Zones on Growth Parameters and Proximate Composition of Sesame - Oloyede, Funmilayo Mary; Alade, Tawakalitu Ibukun; Daramola, Gabriel Gbenga; Abdulrasheed, Hawaw (Khwopa Journal, 2025)
Sesame (Sesamum indicum L.) is one of the oldest cultivated oilseed crops, valued for its high nutritional content and adaptability to diverse environmental conditions. In Nigeria, sesame is grown across different agroecological zones; however, there is limited research on how cultivar selection and environmental factors collectively affect its growth and nutritional properties. This study aimed to evaluate the growth performance and proximate composition of different sesame cultivars across varying agroecological conditions. Three sesame cultivars: White Benue, Cameroon White, and E8 were cultivated in two agroecological zones: The experiment was conducted in Ejigbo (a derived savanna) and Osogbo (rainforest) in 2023. Ejigbo is a town in Osun State that is part of the Derived savanna agroecological zone in southwest Nigeria. Osogbo is the capital city of Osun State and is part of a rainforest agro-ecological zone in south-west Nigeria. A randomized complete block design on a plot with four replicates was implemented. Growth parameters, including plant height, stem girth, number of leaves, and leaf area, were measured. Additionally, proximate composition (moisture content, ash, fibre, fat, protein, carbohydrate and calories) was analyzed. Data collected were analysed using Analysis of Variance and Duncan’s Multiple Range Test (DMRT) at a 5% probability level. Results indicated that growth parameters such as plant height and stem girth increased by agroecological conditions, whereas proximate composition exhibited minimal variation across cultivars locations. The increase in plant heigh and stem girth shows that environmental conditions have a greater influence on sesame growth parameters than on its proximate composition. Cameroon White emerged as the most suitable sesame cultivar overall due to its consistently superior performance in plant height, stem girth, leaf number, leaf area, and nutritional content across both locations. Osogbo proved to be the more favorable location for sesame cultivation, as it consistently supported better vegetative growth and higher nutritional quality compared to Ejigbo. It is recommended that sesame farmers prioritize the cultivation of Cameroon White variety, particularly in the Osogbo agroecological zone or similar environments, to optimize plant growth, yield, and nutritional value.